Economic feasibility of marine renewable energy: Review - Bhuiyan, Miraj Ahmed; Hu, Ping; Khare, Vikas; Hamaguchi, Yoshihiro; Thakur, Barun Kumar; Rahman, Muhammad Khalilur (Frontiers in Marine Science, 2022)
This paper aims to comprehensively review the economic feasibility of Marine Renewable Energy. Five major continents are at different development stages of implementing MREs commercialization; Europe is in the most advanced, while Africa is at the initial stage. The Levelized Cost of Energy is usually used to make decisions and measure the plant’s economic feasibility. Literature suggests that MRE technology is still costly, and many emerging countries are sensitive to the income and use of MRE. Among various types of MREs, wind energy is the most feasible for many countries. Offshore wave energy is still at the pre-commercialization stage for many developing countries. Tidal energy plants can be economically viable depending on a reduction in investment cost and high capacity factors. Most of the world’s tidal flows have too low a speed to operate a turbine of commercial size for ocean thermal energy. In conclusion, the factors hindering MRE development are pointed out, and future challenges are discussed.